FRI0650-HPR Comparison of The Effectiveness of Functional and Night Splint for Rhizarthrosis: A Controlled, Randomized, Blinded Clinical Trial. (15th July 2016) - Silva, F.C.; Adolph, S.M.M.; Timoteo da Silva, R.V.; Natour, J.
Abstract : Background: Rhizarthrosis is an inflammatory degenerative joint disease affecting the trapeziometacarpal joint of the thumb that impairs lateral pinching and movements of opposition and retroposition. The main symptom is pain, leading to difficulty with hand functions and reduced quality of life. Immobilization of the trapeziometacarpal joint of the thumb by splint has proved effective in reducing pain and improving hand function in patients suffering from the condition. Two randomized controlled trials found in the literature reported similar findings in terms of pain reduction and improved hand function with the use of a short orthosis for rhizarthrosis; one of the trials showed the benefits when the device was used for daytime function while the other showed the benefits when the orthosis was used during nighttime rest. Objectives: To compare the effectiveness of functional (daytime) and night splint (Figure 1 ) in reducing pain and improving functionality in patients with rhizarthrosis. Methods: A controlled, randomized, blinded clinical trial with sixty patients diagnosed with rhizarthrosis. The patients were assessed by a blinded assessor at the beginning of the treatment and after 45, 90 and 180 days the following variables were evaluated: pain at the base of the thumb using a a numerical pain scale; thumb range of motion measured using a goniometer; grip strength evaluated by a hydraulic hand dynamometer; pinch strength using the pinch gage; hand dexterity evaluated with the pick-up test; function evaluated by the Brazilian version of the AUSCAN LK 3.01 Hand Osteoarthritis Index, the Cochin Hand Function Scale, the Michigan Hand Outcomes Questionnaire and a Likert-type scale. The Hand Outcomes Questionnaire, Cochin Scale and Michigan Questionnaire were used to assess hand function and patient satisfaction using a Likert scale. Results: Most of the variables analyzed, including patient characteristics such as age, gender, disease duration and hand dominance, were homogeneous at the beginning of the study. In both groups there was a reduction in hand pain with time (intragroup analysis). Pain in the functional group, expressed as mean ± standard deviation, was 6.82±1.72 and 4.77±2.45 at the beginning and end of the treatment, respectively, and the corresponding figures for the nighttime group were 7.20±1.63 and 4.83±2.68. The p values for both groups were p<0.001. There were no statistically significant differences in the majority of the parameters assessed between the groups. The only domains with a statistically significant difference (p<0.001) between the two groups were: activities of daily living in the AUSCAN questionnaire and satisfaction in the Michigan questionnaire, for both of which the functional group had better scores Conclusions: There was no statistically significant difference between functional and night splint in terms of pain, function or any of the other parameters assessed in rhizarthrosis patients. References: Carreira ACG, Jones A, Natour J. Assessment of the effectiveness of a functional splint for osteoarthritis of the trapeziometacarpal joint of the dominant hand: a randomized controlled study. J Rehabil Med 2010;42(5): 469–74; Rannou F, Dimet J, Boutron I, et al. Splint for Base-of-Thumb Osteoarthritis. A randomized trial. Annals of Internal Medicine 2009;150(10):661–9; Disclosure of Interest: None declared